2002
DOI: 10.1007/s00441-002-0554-7
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal muscle of sheep is innervated by non-polarized pathways of cholinergic and nitrergic myenteric neurones

Abstract: The motility patterns of the reticulorumen evoke mainly mixing of the ingesta. So far unknown, intrinsic neural circuits of the enteric nervous system are involved in the control of these motility patterns. The aim of the study was to characterize neurochemically sheep ruminal myenteric neurones, in particular the neural pathways innervating the ruminal muscle layers. Cell bodies within the myenteric plexus projecting to the longitudinal or circular muscle layer were retrogradely labelled by direct application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 27 publications
5
52
0
Order By: Relevance
“…We consider that the ENS cells stained with the general markers (NSE and Hu) probably represent a large proportion of the neuronal population on the basis of the specificity of these markers for neuron-specific protein in other species. In addition, the anti-NSE antibody is generally accepted to stain the entire neuronal population of the sheep ENS (Pfannkuche et al 2002). Our personal observations of the validity of NSE and Hu staining have shown that the anti-NSE antibody stains about 98% of the Hu-IR neurons and that 100% of the Hu-stained cells are NSE-IR, suggesting that both are good pan-neuronal markers of sheep enteric neurons.…”
Section: Whole-mountsmentioning
confidence: 92%
See 2 more Smart Citations
“…We consider that the ENS cells stained with the general markers (NSE and Hu) probably represent a large proportion of the neuronal population on the basis of the specificity of these markers for neuron-specific protein in other species. In addition, the anti-NSE antibody is generally accepted to stain the entire neuronal population of the sheep ENS (Pfannkuche et al 2002). Our personal observations of the validity of NSE and Hu staining have shown that the anti-NSE antibody stains about 98% of the Hu-IR neurons and that 100% of the Hu-stained cells are NSE-IR, suggesting that both are good pan-neuronal markers of sheep enteric neurons.…”
Section: Whole-mountsmentioning
confidence: 92%
“…We have observed that CGRP-IR fibres make contacts with TK-IR, VIP-IR or NOS-IR neurons. TK-IR neurons seem to play a motor functional role in the sheep ENS, whereas VIP/NOS neurons seem to play an inhibitory role (Pfannkuche et al 2002) and so we can speculate that CGRP-IR Dogiel type II neurons play a physiological sensory role and act on both excitatory and inhibitory motor neurons.…”
Section: Cgrp-ir Fibresmentioning
confidence: 98%
See 1 more Smart Citation
“…The specificity of rat anti-SP was tested using the adsorption test (Pfannkuche et al, 2002) which, in past unpublished experiments, had been found to be totally colocalized with the rabbit anti-SP antibody employed (see Table 1). We did not test the specificity of rabbit anti-NF200 kDa antibody (Sigma, cod.…”
Section: Specificity Of Antibodiesmentioning
confidence: 99%
“…Acetylcholine as well as SP cause a contraction of the smooth muscle layers in the forestomach (Vassileva et al, 1978;Veenendaal et al, 1982). Retrograde tracing studies have obtained evidence that neurones immunoreactive for ChAT and SP directly take part in the innervation of ruminal smooth muscle layers (Pfannkuche et al, 2002). In our study most neurones that were not immunoreactive for acetylcholine expressed immunoreactivity for NOS and VIP.…”
Section: Discussionmentioning
confidence: 49%